The Gender Equality in Education According to Quran : Analysis of Women's Educational Access Rights - Gintari, Ayu; Abubakar, Achmad; Mardan (Jurnal Ilmiah Edukatif, 2025)
The issue of gender equality in education remains a multidimensional problem encompassing theological, social, and cultural aspects. Although Islam normatively affirms the spiritual and intellectual equality between men and women, empirical realities within many Muslim societies continue to reflect patriarchal biases that restrict women’s access to education. This study aims to analyze the concept of gender equality in education based on the Qur’anic perspective, emphasizing women’s rights to acquire knowledge. Employing a qualitative approach through thematic interpretation (tafsīr maudhū‘ī) and the sociology of education framework, the study finds that the Qur’an regards education as a universal human right, not limited by gender. The persistence of inequality stems not from Islamic teachings but from socio-cultural structures and patriarchal interpretations of religious texts. Within this framework, Islamic education should function as a means of liberation, in line with Paulo Freire’s critical pedagogy, by fostering critical consciousness against social and gender injustices. The findings imply the need for reformulating Islamic education curricula with a gender-equitable perspective, strengthening teachers’ gender awareness, and developing contextual Qur’anic interpretations. Such reforms are essential to transform Islamic education into an instrument for building a civilized, egalitarian, and socially just society.